Rancang Bangun Water Seal Drainage (WSD) Khusus Thorax - Diah Rahayu Ningtias; Bayu Wahyudi; Iqbal Firdaus (Jurnal Teori dan Aplikasi Fisika, 2020)
A Water Seal Drainage (WSD) design was made to remove air and fluid from the pleural cavity in the thorax (lung cavity) using a connecting tube or chest tube to maintain the negative pressure of the cavity. Under normal circumstances, the pleural cavity has negative pressure and only a little pleural fluid is filled. Suction pumps have a high pressure with a pressure range of -10 kPa to -80 kPa. The pressure is large enough so that it is not suitable for thorax because it can cause damage to internal organs due to high pressure. WSD specifically for thorax has a low pressure which is below -5 kPa / -40 mmHg. This WSD is equipped with a hand switch, water level and automatic Arduino Uno based exhaust system which has a pressure below -26.6 kPa / -20 cmHg to suction and pressure below -3.4 kPa / -2.6 cmHg to remove liquid from the bottle . The hand switch itself functions as a manual control to make it easier for the user, while the level sensor functions as a safety level for fluid levels in the tool and also an automatic fluid disposal system so that it is more efficient.